Lack of Parkinsonian Pathology and Neurodegeneration in Mice After Long-Term Injections of a Proteasome Inhibitor in Olfactory Bulb and Amygdala - del Rey, Natalia Lopez-Gonzalez; Balzano, Tiziano; Martin-Rodriguez, Lucia; Salinas-Rebolledo, Constanza; Trigo-Damas, Ines; Rojas-Fernandez, Alejandro; Alvarez-Erviti, Lydia; Blesa, Javier (Frontiers in Aging Neuroscience, 2021)
Proteinaceous inclusions, called Lewy bodies, are used as a pathological hallmark for Parkinson's disease (PD). Recent studies suggest a prion-like spreading mechanism for α-synucleinopathy where early neuropathological deposits occur, among others, in the olfactory bulb and the amygdala. Lewy bodies contain insoluble α-synuclein and many other ubiquitinated proteins, suggesting a role of protein degradation system failure in PD pathogenesis. Therefore, we wanted to study the effects of a proteasomal inhibitor, lactacystin, in the aggregability and transmissibility of α-synuclein in the olfactory bulb and amygdala. We performed injections of lactacystin in olfactory bulb and amygdala of wild type mice. Motor behavior, markers of neuroinflammation, α-synuclein, and dopaminergic integrity were assessed by immunohistochemistry. Overall, there were no differences in neuron number and α-synuclein expression in these regions following injection of lactacystin into either the olfactory bulb or amygdala. Microglia and astroglial labeling appeared to be correlated with surgery induced inflammation or local effects of lactacystin. Consistent with the behavior and the pathological findings, there were no loss of dopaminergic cell bodies in the substantia nigra and terminals in the striatum. Our data showed that long-term lactacystin injections in extra nigrostriatal regions may not mimic spreading aspects of PD and reinforce the special vulnerability of the dopaminergic neurons of the substantia nigra pars compacta.